Varying reasons of young learners’ problem behaviours according to novice ELT teachers - Tunaz, Mehmet (Journal of Human Sciences, 2017)
This research is conducted to examine novice ELT teachers’ perspective on the possible motives behind young learners’ problem behaviours in English classes. The gender of ELT teachers have been also considered in order to investigate whether there is a difference between the perception of male and female teachers on the leading causes of problem behaviours in classroom. The adapted version of the questionnaire developed by Miller, Ferguson & Byrne (2000) were conducted with 15 male and 15 female novice teachers in their first year in teaching profession. The result of the study indicated that both male and female novice teachers have similar ideas about the causes of misbehaviour except for one point: (1) teachers’ rewards and punishments. Female teachers stated that teachers’ rewards and punishment might be the main motive for problem behaviours whereas male teachers disregard this factor as a crucial cause of misbehaviour. As for the other three factors, all the teachers agreed that (2) “adult behaviour” and (3) “curriculum demands on children” might increase the frequency of misbehaviour among young learners in English classes. (4) “Personality of the learner”, however, was found to be the most important reason behind problem behaviours. As the results revealed, most of the factors were explained similarly by both male and female teachers except for teachers’ rewards and punishments, a finding which shows that gender has little (if any) effect on novice teachers’ attribution for learner misbehaviour in EFL classes.